The profile of BMI, visceral fat, and blood pressure between stunting and non-stunting in school-age children - Widjaja, Nur Aisiyah; Devaera, Yoga; Medise, Bernie Endyarni; Julia, Madarina; Sitaresmi, Mei Neni; Asmarinah; Kalalo, Royke Tony; Soesanti, Frida; Friska, Dewi; Santoso, Febrina Mustika; Ardianah, Eva; Ulfa, Wilda Fauzia (Acta Biomedica Atenei Parmensis, 2025)
Background and Objectives: Stunting is a prevalent type of malnutrition that frequently affects in school-age children. The prevalence of stunting among school-age children in Indonesia was 30.7% among children aged 5–12 and 35.1% among children aged 13–15. Early stunting is considered as a contributing factor for the development of overweight and adiposity in later stages of life. Rapid growth also provides adverse consequences for stunting children in long-term health, such as a higher risk of developing hypertension. This study is performed to determine the profile of BMI, visceral fat and blood pressure between stunting and non-stunting in school-age children.Methods: A case control study involving 191 children aged 8 years for the female and 9 years for the male. The subjects divided into two group according to HAZ status: stunting (HAZ score 1.64). Results: Study groups consisted of stunting (98 subjects) and non-stunting group (93 subjects). Stunting children had significant higher BMI, BMI-for-age-z-score, waist circumference, visceral fat and total body fat, also less upper arm circumference, muscle mass, muscle quality, basal metabolic rate and bone mass compared to non-stunting children. Boys in non-stunting group showed significant higher body weight, body height and muscle mass. Stunting girls showed highest BMI and visceral fat. There was a significant association between HAZ score with BMI and visceral fat, but no association with blood pressure.Conclusion: Stunting children was correlated with higher profile of BMI and visceral fat but had no difference or correlation with both systolic and diastolic blood pressure. Overweight and obesity was more frequent in stunting girls.